Sports economics and big data: A revolution in sports performance analysis - Merah, Nourelhouda; Ouissam, Deboub (The International tax journal, 2025)
This study aims to elucidate the role of big data in advancing sports economics and performance analysis while also examining the impact of artificial intelligence and machine learning on the sports industry. These findings underscore the benefits that these technologies can provide in enhancing sporting strategies and increasing financial returns. The research examined the experiences of clubs such as Liverpool, the Houston Rockets, the Oakland Athletics, and the Golden State Warriors, all of which have benefited from advanced analytics in player recruitment, tactical planning, injury management, and competitor analysis. The study concludes that the application of big data in the sports sector contributes to improving team and athlete performance through the analysis of biometric and physiological data. This further facilitates more precise decision-making, reduces the incidence of injuries, and strengthens sports marketing strategies, thereby increasing financial returns. Moreover, achieving a balance between data collection and the protection of athletes' privacy represents a significant challenge, necessitating clear legislation to ensure the ethical use of data.